1991
DOI: 10.1080/08858199109528086
|View full text |Cite
|
Sign up to set email alerts
|

Induced versus spontaneous attendance of breast-screening tests by women

Abstract: Despite the availability of services and information, not enough women undergo breast-screening tests. A previous study showed that clinic attenders differ from nonattenders in emotions, personality, self-concept, neuroticism, psychosomatics, and health attitudes. Some of these resembled the cancer-prone personality. The present study was designed to test whether nonattenders have higher repression that supports denial and could be persuaded by positive inducements to undergo the tests. Other goals were to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…11 – 15 Two studies focused on the association between neuroticism or extraversion and cancer screening visiting (attendance 1 or more times vs. no attendance). One study reported that neuroticism was not significantly associated with breast cancer screening visiting, 13 which is consistent with our results. However, we found that neuroticism score was significantly associated with gastric cancer screening compliance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…11 – 15 Two studies focused on the association between neuroticism or extraversion and cancer screening visiting (attendance 1 or more times vs. no attendance). One study reported that neuroticism was not significantly associated with breast cancer screening visiting, 13 which is consistent with our results. However, we found that neuroticism score was significantly associated with gastric cancer screening compliance.…”
Section: Discussionsupporting
confidence: 93%
“…11 , 12 Personality is another factor that might influence attendance. Breast cancer screening attendees tended to have a higher score in extraversion, 13 and a lower score in neuroticism, 14 than non-attendees. 13 , 14 However, one study showed no association between personality and gastric cancer screening attendance.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies found that the personality traits of extraversion and neuroticism were significantly associated with cancer screening attendance 46–48. This study demonstrates that personality traits influence prehospital delay.…”
Section: Discussionsupporting
confidence: 61%